2017
DOI: 10.1002/2017jd026731
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of Heat Stress Due To Global Warming in South Korea Based on Multi‐RCM Ensemble Projections

Abstract: This study assesses the future changes in summer (June–July–August; JJA) heat stress over South Korea under global warming. To better resolve the region‐specific changes in terms of geographical patterns and severity of heat stress in the Korean peninsula, four regional climate models (RCMs) are used for dynamical downscaling of Hadley Centre Global Environmental Model version 2—Atmosphere and Ocean global projections forced by two Representative Concentration Pathway (RCP4.5 and RCP8.5) scenarios. Dynamically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…It is also equally important to consider ambient humidity because humans are sensitive to the combination of temperature and humidity (Steinweg and Gutowski 2015, Pal and Eltahir 2016, Im et al 2017b. Therefore, we also investigate the characteristics of WBGT that is widely used to measure the heat stress and accompanied risk level (Willett and Sherwood 2012, Im et al 2017a. Figure 5 presents WBGT and daily mean temperature and daily mean relative humidity (RH) used to calculate WBGT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also equally important to consider ambient humidity because humans are sensitive to the combination of temperature and humidity (Steinweg and Gutowski 2015, Pal and Eltahir 2016, Im et al 2017b. Therefore, we also investigate the characteristics of WBGT that is widely used to measure the heat stress and accompanied risk level (Willett and Sherwood 2012, Im et al 2017a. Figure 5 presents WBGT and daily mean temperature and daily mean relative humidity (RH) used to calculate WBGT.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the projected changes at the global scale such as a virtually certain increase in the frequency and magnitude of unusually warm days and nights (IPCC 2013), recent studies based on climate modeling have demonstrated that the statistical likelihood of extreme hot temperatures and heatwaves in Korea is also projected to increase due to global warming (Lee 2017, Im et al 2015, 2017a, Shin et al 2018. Most of these studies have focused on comparative analysis to show how much future climate in response to enhanced greenhouse gas emissions (GHGs) will depart from the reference climate in response to historical GHGs.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The critical role of extreme heat with respect to many different crops has been reported, with a particular emphasis on the disproportionately negative impacts of the accumulation of extreme heat on agriculture production (Schlenker and Roberts, 2009). The intensity and frequency of extreme temperature during summer in South Korea have gradually increased in accordance with rising global mean temperature (Im et al, 2015(Im et al, , 2017. As global warming accelerates, the uncommonly high Tmax under the current climate is likely to become increasingly normal (Im et al, 2017(Im et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%